1994
DOI: 10.1007/bf02257793
|View full text |Cite
|
Sign up to set email alerts
|

Early postoperative feeding

Abstract: Early postoperative feeding is safe and is tolerated by the majority of patients. Early feeding, if tolerated, decreases length of hospital stay and may decrease health care costs. Longer operative time and increased blood loss intraoperatively may indicate a more difficult procedure and identify those patients who will not tolerate early feeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(42 citation statements)
references
References 18 publications
3
37
0
2
Order By: Relevance
“…Dentro deste contexto, trabalhos experimentais demonstraram que a realimentação precoce, na verdade, favorece a cicatrização de anastomoses intestinais 11,12 . Progressivamente, o medo do retorno precoce da dieta em pós-operató-rios envolvendo anastomoses digestivas vem ficando cada vez menor entre os cirurgiões na medida que a realimentação precoce, quando testada, parece ser segura segundo alguns autores [1][2][3][13][14][15] . Da mesma maneira, nas operações sobre o aparelho digestivo, muitos cirurgiões já não adotam mais como rotina a permanên-cia da sonda naso-gástrica durante todo o período de íleo paralítico 15,16 .…”
Section: Discussionunclassified
“…Dentro deste contexto, trabalhos experimentais demonstraram que a realimentação precoce, na verdade, favorece a cicatrização de anastomoses intestinais 11,12 . Progressivamente, o medo do retorno precoce da dieta em pós-operató-rios envolvendo anastomoses digestivas vem ficando cada vez menor entre os cirurgiões na medida que a realimentação precoce, quando testada, parece ser segura segundo alguns autores [1][2][3][13][14][15] . Da mesma maneira, nas operações sobre o aparelho digestivo, muitos cirurgiões já não adotam mais como rotina a permanên-cia da sonda naso-gástrica durante todo o período de íleo paralítico 15,16 .…”
Section: Discussionunclassified
“…Experimental models contribute to patients' postoperative discomfort, and for investigating postoperative ileus are needed. In occasionally, prolonged nasogastric suction or even reparticular, recording of postoperative colonic motility laparotomy is needed [1,3]. In addition, the time point in awake rats has not been described yet.…”
mentioning
confidence: 98%
“…Furthermore, a recent study has also demonstrated the safety of early oral feeding within 24 h of receiving major upper gastrointestinal surgery such as gastrectomy and Whipple's procedures [7] . Withholding nutrition from patients until the resolution of the transient postoperative ileus has been employed as the standard postoperative management for well over 100 years [11] , and is thought to have developed in response to the high rates of postoperative emesis experienced by patients anaesthetised with traditional agents, such as ether and chloroform [12] . From this origin, a cautious reintroduction of diet following operative procedures has been adopted, irrespective of the site of surgery, and particularly so if it has involved the gastrointestinal tract [12] .…”
Section: Editorialmentioning
confidence: 99%
“…Withholding nutrition from patients until the resolution of the transient postoperative ileus has been employed as the standard postoperative management for well over 100 years [11] , and is thought to have developed in response to the high rates of postoperative emesis experienced by patients anaesthetised with traditional agents, such as ether and chloroform [12] . From this origin, a cautious reintroduction of diet following operative procedures has been adopted, irrespective of the site of surgery, and particularly so if it has involved the gastrointestinal tract [12] . A textbook on surgical aftertreatment from 1915 recommends "feed(ing) the patient as soon as possible, but at the same time to avoid distension" for patients undergoing abdominal surgery, for which a clear fluid diet (consisting of water, tea and sparkling wine) is promoted in the first few days post surgery, followed by boiled fish or eggs after "a day or two" [13] .…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation